RANCANGAN MONITORING ALARM TRANSMISSION OIL LEVEL PADA GEARBOX RADAR BERBASIS ESP8266 DENGAN NOTIFIKASI TELEGRAM - Syifa Azzahra, Wahyuni; Toni; Purwanto, Medy (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
Radar (Radio Detection and Ranging) is a critical tool used by AirNav Indonesia for surveillance services. Regular maintenance of radar equipment, including daily, weekly, monthly, and annual inspections, is essential to ensure operational reliability. This study aims to design and implement a real-time oil level monitoring system for radar gearbox units using an ESP8266 microcontroller and the Telegram messaging platform. The system utilizes a TCRT5000 optical sensor to detect oil levels and triggers an alarm when the level falls below a predefined threshold. The data is processed by a NodeMCU and transmitted via Wi-Fi to notify users through Telegram. System performance was evaluated through simulated variations in oil level, successfully generating real-time alerts. The proposed monitoring system enhances preventive maintenance efforts and helps reduce the risk of gearbox damage